Kemampuan Siswa Kelas VIII SMP Negeri 18 Banda Aceh Mengidentifikasi Unsur-Unsur Teks Berita - Muhammad Idham; Azhari Azhari (Master Bahasa, 2022)
The study aimed to find out and describe the ability of students of class VIII at SMP Negeri 18 Banda Aceh (what, who, when, where, why, and how) that was read. The population of this research is the eighth grade students of SMP Negeri 18 Banda Aceh, the 2018-2019 school year is 161 people and the sample of this study is 32 students. The method used in this research is quantitative descriptive method. Research data were collected through nontest techniques. analyzing data using simple statistical techniques, namely quantitative. The results showed that the ability of eighth grade students of SMP Negeri 18 Banda Aceh to identify elements of the news text was 74.25, the average value included in both categories. The average value obtained by students is (a) identifying which elements received a score of 91.15 and included in the category of very good, (b) identifying the elements who got a score of 75 and included in the category of good, (c) identifying the elements in which the score 79 and included in the good category, (d) identified the element when it got a score of 100 and included in the very good category, (e) identified the element why it got a score of 67.03 and included in the enough category, (f) identified the element how to get a score of 57 and included in the category enough. Overall the results of the study showed that the scores obtained by students in the excellent range amounted to 10 students (31.25%), in the good category there were 8 students (25%), in the sufficient category there were 9 students (28.12%), in the category less than 5 students (15.25%), and in the category of very few there are 0 students (0%). Thus, the ability of eighth grade students of SMP Negeri 18 Banda Aceh to identify elements of the news text is in the very good category because it meets the minimum completeness criteria, namely: 73